The Effect of Wheat Flour With Singapore Banana Flour (Musa Sp) Substitution on The Physicochemical and Organoleptic Characteristics of Cookies - Walimah, Walimah; Priyono, Suko; Maherawati, Maherawati (FoodTech: Jurnal Teknologi Pangan, 2024)
Singapore banana (Musa spp) is the local name for the 40-day banana. Other types of bananas that are similar to Singapore bananas are barlin and berlin bananas. Cookies are a bakery product that is popular in all circles and is widely consumed by the public because it has an attractive taste and shape. The aim of this research is to find out the right formulation to produce Singapore banana flour and wheat flour cookies. The characteristics observed include water content, ash, potassium, vitamin C, color value and organoleptic tests. This research design used the Randomized Block Design (RAK) method which consisted of 6 treatments with the formulation of wheat flour : Singapore banana flour, namely (100% : 0%), (80% : 20%), (60% : 40%), (40% : 60%), (20% : 80%) and (0% : 100%). Data on physicochemical characteristics were analyzed using the ANOVA test at 5% level, if it had an effect, it was continued with the Honestly Significant Difference (BNJ) test at 5% level, while the organoleptic test was analyzed using the Kruskal Wallis method and the effectiveness index test using the De Gharmo method. Based on the research results, it can be concluded that the use of Singapore banana flour as an ingredient for making cookies with a formulation of 60% added wheat flour with 40% Singapore banana flour is the best formulation. The resulting cookies contain water content 6,38%, ash content 2,50%, potassium 512,5 mg/100 g, vitamin C 0,574 mg/100 g, color L* worth 43,13, color a* worth 5,38, color b* is worth 16,2. The best organoleptic tests for cookies were color score 3,87 (somewhat like), aroma score 3,77 (somewhat like), texture score 4 (like) and taste score 4 (like).